Integrated Fecal Microbiome and Metabolomics Reveals a Novel Potential Biomarker for Predicting Tibial Dyschondroplasia in Chickens - Huang, Shucheng; Zhang, Chaodong; Xu, Tingting; Shaukat, Aftab; He, Yanfeng; Chen, Pan; Lin, Luxi; Yue, Ke; Cao, Qinqin; Tong, Xishuai (Frontiers in Physiology, 2022)
Tibial dyschondroplasia (TD) is a metabolic tibial-tarsal disorder occurring in fast-growing poultry, and its diagnosis is mainly based on an invasive method. Here, we profiled the fecal gut microbiome and metabolome of broilers with and without TD to identify potential non-invasive and non-stress biomarkers of TD. First, TD broilers with the most pronounced clinical signs during the experiment were screened and faecal samples were collected for integrated microbiome and metabolomics analysis. Moreover, the diagnostic potential of identified biomarkers was further validated throughout the experiment. It was noted that the microbial and metabolic signatures of TD broilers differed from those of normal broilers. TD broilers were characterized by enriched bacterial OTUs of the genus Klebsiella, and depleted genera [Ruminococcus], Dorea, Ruminococcus, Oscillospira, Ochrobactrum, and Sediminibacterium. In addition, a total of 189 fecal differential metabolites were identified, mainly enriched in the purine, vitamin and amino acid metabolism, which were closely associated with differential microbiota and tibia-related indicators. Furthermore, three fecal metabolites were screened, including 4-hydroxybenzaldehyde, which distinguished TD from normal broilers with extremely high specificity and was superior to serum bone markers. These results indicated that gut microbiota equilibrium might influence the pathogenesis of TD by modulating host metabolism, and the identified fecal metabolite 4-hydroxybenzaldehyde might be a potential and non-invasive biomarker for predicting TD in chickens.